TOKOH DAN PENOKOHAN DALAM TEKS CERITA FANTASI KARYA SISWA KELAS VII SMP NEGERI 1 PAYAKUMBUH - Jumesa, Elin Novia; Abdurahman, Abdurahman; Emidar, Emidar (Jurnal Pendidikan Bahasa dan Sastra Indonesia, 2018)
This article aims to describe the following two points. First, describe the types of characters in the text of fantasy stories of students of class VII SMP Negeri 1 Payakumbuh. Second, describe the technique of the presence of characters in the text of fantasy stories of students of class VII SMP Negeri 1 Payakumbuh.The type of research used is qualitative research using descriptive method. The instrument of this research is the researcher / writer himself assisted the theoretical books and tables of data analysis. This research data is a language tool in the form of written words taken from the data source. The data in the form of figures and techniques of the presence of characters contained in the text of fantasy stories of students of class VII SMP Negeri 1 Payakumbuh which amounted to 30 texts. The technique of data validation used is triangulation technique. The data analyzing steps are: (1) identifying the general picture of data as well as encoding text, (2) coding the data, (3) analyzing the characters and characterizations in the fantasy story text of the students of grade VII SMP Negeri 1 Payakumbuh by using formats based on theory used, (4) discussion of research data, (5) summarizes the results of research, and (6) reported the results of research in the form of thesis. Based on the research results can be concluded two things. First, the kind of characters that tend to be used by students of grade VII SMP Negeri 1 Payakumbuh in the fantasy story text that they write is a fictional character, additional characters, white figures, flat figures, and static figures. Second, the technique of presence of characters that tend to be used students of class VII SMP Negeri 1 Payakumbuh in the text of the fantasy story they write is analytical techniques, action techniques, and techniques of words.Â Kata kunci: Tokoh, Penokohan, Teks Cerita Fantasi